Solanum Xanthocarpum: The Unexplored Drug In Managing Urolithiasis- A Case Report (Advancements in Homeopathic Research, 2025)
Urolithiasis, renal stones, kidney stones are used  interchangeably to refer to the accretion of hard, solid  , non metallic minerals in urinary tract. Different  regions of India have varying stone compositions,  however there aren't many extensive prospective  studies to offer accurate figures.Males are more likely  than females to develop urinary stones at all ages.  Calcium oxalate is the most common component  of urinary stones in Northwestern Rajasthan,  regardless of age group. Calculi that are associated  with obstruction, renal failure, and infection requires  further critical interventions.Treating urolithiasis  through organopathic prescription in homoeopathy  can beneficial to avoid unwanted complications as in  modern line of treatment. Solanum Xanthocarpum, an  unexplored drug in field of homoeopathy has shown  beneficial results in treating calculi in other systems  of medicine. Charak has recommended its use in  piles, cough, delirium tremens and calculi expulsion.  Shushruta has found its effectiveness in ophthalmia  and urinary strictures. Bangasena has recommended  its use in cough of children. According to Dr. SC  Ghosh Solanum Xanthocarpum is unquestionably a  grand medicine in suppression of urine, stricture and  calculi explusion and formation. In the cure of these  maladies, Solanum Xanthocarpum can be compared  with Berberis Vulgaris, Cantharis, Sarsaparilla and  lycopodium. This case report enhances the knowledge  regarding Solanum Xanthocarpum, its constituents  and its beneficial results clinically in treating patient  suffering from urolithiasis which is evident through  investigations reports of the patient.
Keywords: Homoeopathy; Urolithiasis; Organopa